Taxonomy and ecology of Synedropsis roundii sp. nov. (Bacillariophyta) from a tropical brackish coastal lagoon, south-eastern Brazil - Melo, Sérgio; Torgan, Lezilda Carvalho; M., Menezes; Huszar, Vera Lúcia de Moraes; Corrêa-Junior, José D.; Bozelli, Reinaldo Luiz (Phycologia, 2003)
A new Synedropsis species is described from a coastal tropical lagoon in south-eastern Brazil. This species has a single chloroplast in both views of the valve, apical pore fields composed of three slits, and uniseriate striae. It is planktonic and was found in brackish water. Synedropsis roundii is the eighth Synedropsis species to be described and the first to be found in a tropical region. We studied the seasonal dynamics of S. roundii, which can form blooms in the coastal Imboassica Lagoon, Rio de Janeiro state, Brazil. Continuous mixing of this shallow environment is suggested to be an important physical factor determining the success of the species. Availability of soluble reactive silicon is thought to be the main factor regulating the large biomass fluctuations. In the classification of Reynolds in 1997 (Vegetation processes in the pelagic: a model for ecosystem theory. Ecology Institute, Oldendorf, Germany, 371 pp.), S. roundii appears to belong to D-assemblage, a set of small and fast-growing diatoms, well represented in small, shallow and enriched waters. We also offer a tentative habitat template for S. roundii.
Keywords: Algae; Bacillariophyta; Eukaryota; Synedropsis; Synedropsis Roundii